Electronic and Structural Engineering of Carbon‐Based Metal‐Free Electrocatalysts for Water Splitting - Wang, Xuesi; Vasileff, Anthony; Jiao, Yan; Zheng, Yao; Qiao, Shi‐Zhang (Advanced materials (Weinheim), 2019)
Since first being reported as possible electrocatalysts to substitute platinum for the oxygen reduction reaction (ORR), carbon‐based metal‐free nanomaterials have been considered a class of promising low‐cost materials for clean and sustainable energy‐conversion reactions. However, beyond the ORR, the development of carbon‐based catalysts for other electrocatalytic reactions is still limited. More importantly, the intrinsic activity of most carbon‐based metal‐free catalysts is inadequate compared to their metal‐based counterparts. To address this challenge, more design strategies are needed in order to improve the overall performance of carbon‐based materials. Herein, using water splitting as an example, some state‐of‐the‐art strategies in promoting carbon‐based nanomaterials are summarized, including graphene, carbon nanotubes, and graphitic‐carbon nitride, as highly active electrocatalysts for hydrogen evolution and oxygen evolution reactions. It is shown that by rationally tuning the electronic and/or physical structure of the carbon nanomaterials, adsorption of reaction intermediates is optimized, consequently improving the apparent electrocatalytic performance. These strategies may facilitate the development in this area and lead to the discovery of advanced carbon‐based nanomaterials for various applications in energy‐conversion processes. Carbon‐based nanomaterials are expected to be cost‐effective alternatives to noble‐metal electrocatalysts and have become a hot research field in recent years. Strategies for designing carbon‐based electrocatalysts for water splitting are summarized. Electronic and structure engineering procedures that are used to tune the activity of the carbon materials are presented systematically to provide guidance for future research.